Maternal and Fetal Factors Associated with Mortality and Morbidity in a Multi-Racial/Ethnic Registry of Anti-SSA/Ro Associated Cardiac Neonatal Lupus - Izmirly, Peter M. (2011)
BACKGROUND: Cardiac manifestations of neonatal lupus (cardiac-NL) include conduction disease and rarely an isolated cardiomyopathy. This study was initiated to determine the mortality and morbidity of cardiac-NL and associated risk factors in a multi-racial/ethnic US-based registry to provide insights into the pathogenesis of antibody mediated injury and data for counseling. METHODS AND RESULTS: Three hundred and twenty-five offspring exposed to maternal anti-SSA/Ro antibodies with cardiac-NL met entry criteria. Maternal, fetal echocardiographic, and neonatal risk factors were assessed for association with mortality. Fifty-seven (17.5%) died; 30% in utero. The probability of in utero death was 6%. The cumulative probability of survival at 10 years for a child born alive was 86%. Fetal echocardiographic risk factors associated with increased mortality in a multivariable analysis of all cases included hydrops and endocardial fibroelastosis (EFE). Significant predictors of in utero death were hydrops and earlier diagnosis, and for postnatal death, hydrops, EFE, and lower ventricular rate. Isolated heart block was associated with a 7.8% case fatality rate whereas the concomitant presence of dilated cardiomyopathy or EFE quadrupled the case fatality rate. There was a significantly higher case fatality rate in minorities compared to Caucasians, who were at a lower risk of hydrops and EFE. Pacing was required in 70% and cardiac transplantation in four children. CONCLUSION: Nearly one-fifth of fetuses who develop cardiac-NL die from complications which are predicted by echocardiographic abnormalities consistent with antibody associated disease beyond the AV node. The disparity in outcomes observed between minorities and Caucasians warrants further investigation.